Surface impregnation method of cement hardened body and evaluation method of surface protection state thereof

JP2025033243APending Publication Date: 2025-03-13NAGOYA INSTITUTE OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023138819
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0009】 本発明による表面含浸工法によれば、セメント硬化体の表面に保護層を形成し、既設の環境下でセメント硬化体への劣化因子に侵入を抑制することができる。そして、凍結法によるセメント硬化体の表面保護状態の評価法によって、経時的な複数回の測定操作を要せず、試験後に試験前より測定対象物が吸水した状態に変化することなく、簡便に測定対象物の吸水抵抗性すなわち空隙の閉塞状態を評価(測定)することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025033243000001_ABST
    Figure 2025033243000001_ABST
Patent Text Reader

Abstract

To provide a method in which an impregnating material to be applied to a cement hardened body is colloidal silica, and after application, the cement hardened body can be protected under an existing environment, and to provide a method for evaluating the surface protection state of the hardened cement body, which does not require multiple measurement operations over time and can easily evaluate (measure) the water absorption resistance of a measurement target object, i.e., the blocking state of voids, without causing the measurement target object to change after the test to a state where it has absorbed water compared to before the test, without requiring multiple measurement operations over time.SOLUTION: The present invention relates to a surface impregnation method carried out for protecting the surface of a cement hardened body 1 with a surface impregnation material, and the surface impregnation method includes an impregnation step of impregnating voids 2 formed on a surface 5 of the cement hardened body 1 with colloidal silica as a surface impregnation material, a pH reducing step in which a pH reducing material that reduces pH of the impregnated colloidal silica may come into contact with the colloidal silica after the impregnation step, and / or a contacting step in which chloride ions may come into contact with the impregnated colloidal silica.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a surface impregnation method for hardened cement paste and a method for evaluating (measuring) the surface protection state thereof. [Background technology]

[0002] Surface impregnation is an effective surface protection measure for the urgent maintenance, repair, and reinforcement of concrete structures. Surface impregnation can block voids that form from the surface of the concrete structure toward the inside, improving the water absorption resistance of the concrete structure and protecting the concrete surface. To evaluate the void condition of the hardened cement body, for example, the water absorption resistance of the concrete structure is measured.

[0003] Patent Document 1 describes that a cement-based test specimen is a hardened cement body treated with a surface impregnation material, and colloidal silica and calcium hydroxide (Ca(OH)2) are required as the impregnation material. The test specimen is immersed in pure water at 20°C and the water absorption rate of the test specimen is measured against the immersion time, which is called the Archimedes method, to evaluate the water absorption resistance of the test specimen.

[0004] Non-Patent Document 1 describes that when calcium hydroxide and colloidal silica were applied without the drying process that was previously required, the water absorption resistance was improved compared to silane-based surface impregnation materials. Furthermore, Non-Patent Document 2 describes the conditions for agglomeration of colloidal silica, which requires, for example, hydrochloric acid as a pH adjuster for colloidal silica as an impregnating agent. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2022-79810 [Non-patent literature]

[0006] [Non-Patent Document 1] Jun Kato, Ryutaro Ue, Ryo Yoshida: Study on the effect of interactions caused by combinations of surface impregnation materials on the modification effect, Proceedings of the Cement and Concrete Society, Vol. 74, No. 1, pp. 302-309, March 2021 [Non-Patent Document 2] Ryo Yoshida, Jun Kato, Masaharu Kondo, Masayoshi Fuji, Study on the aggregation and dispersion mechanism of colloidal silica used in surface impregnation materials, Proceedings of the Japan Concrete Institute Annual Conference, Vol. 45, pp. 262-267, July 2023 Summary of the Invention [Problem to be solved by the invention]

[0007] However, the surface impregnation method requires a process of applying calcium hydroxide to the concrete structure in addition to colloidal silica as an impregnating material. In addition, the Archimedes method requires the measurement of water absorption rate over time for the immersed measurement object (specimen) at predetermined time intervals, and the measurement object changes to a state where it absorbs water after the test, making it a destructive test. In addition, the test can only obtain the amount of voids, and no information on the size of the voids (pore diameter or frequency distribution) can be obtained. There were problems. Therefore, in the present invention, the impregnating material to be applied to the hardened cement body is colloidal silica (hereinafter, sometimes simply referred to as "CS"), and a method is provided that can protect the hardened cement body in the existing environment after application. And, as a method for evaluating the surface protection state of the hardened cement body, it is an object to provide an evaluation (measurement) method that does not require multiple measurement operations over time, does not cause the measurement object to change to a state where it absorbs water after the test, and can easily evaluate (measure) the water absorption resistance of the measurement object, i.e., the blocking state of the voids. There are two methods for checking inside the voids: one using a dried sample and the other using a non-dried sample (this invention). This invention applies the non-dried method to check whether a gel that is weak against drying is present inside the voids. [Means for solving the problem]

[0008] The present invention which solves the above problems is as follows. [1] A surface impregnation method for protecting the surface of a hardened cement body with a surface impregnation material, the method comprising: an impregnation step in which colloidal silica, which is a surface impregnation material, is impregnated into voids formed on the surface of the hardened cement body; and a pH reducing step in which a pH reducing material that reduces the pH of the impregnated colloidal silica can come into contact with the colloidal silica after the impregnation step; and / or a contact step in which chloride ions can come into contact with the impregnated colloidal silica. [2] The surface impregnation method according to [1], wherein the pH-reducing agent is a substance that provides hydrogen ions to colloidal silica. [3] The surface impregnation method according to [1], wherein the chloride ions are provided by a salt containing chloride ions. [4] A method for evaluating the surface protection state of a hardened cement body as described in [1], in which the hardened cement body having voids on its surface and containing moisture and the hardened cement body treated with a surface impregnation material are frozen under the same conditions as the hardened cement body and further treated with a surface impregnation material, and the measurement results of the heat flow (mW) of both are compared to evaluate the state of blocking of the voids by the surface impregnation material. [5] The same conditions refer to the evaluation method described in [4], in which freezing is performed at a temperature range of at least 5°C to -50°C. [6] The evaluation method according to [4] or [5], wherein the surface impregnating material is colloidal silica. [7] This is an evaluation method in which, among the peaks detected in the hardened cement body by the evaluation method described in [5], the measurement object for which the lowest temperature peak is not measured is determined to be a hardened cement body treated with an impregnating material. [8] This is an evaluation method in which, among the peaks detected in the hardened cement body by the evaluation method described in [6], the measurement object for which the lowest temperature peak is not measured is determined to be a hardened cement body treated with an impregnating material. Effect of the Invention

[0009] According to the surface impregnation method of the present invention, a protective layer is formed on the surface of the hardened cement body, and it is possible to suppress the intrusion of deterioration factors into the hardened cement body in the existing environment. Furthermore, the evaluation method of the surface protection state of the hardened cement body using the freezing method does not require multiple measurement operations over time, and the measurement object does not change after the test to a state where it has absorbed water compared to before the test, and it is possible to easily evaluate (measure) the water absorption resistance of the measurement object, i.e., the blocking state of voids. [Brief description of the drawings]

[0010] [Figure 1] (a) An example of a surface including voids in reinforced concrete, (b) a schematic diagram showing reinforced concrete having voids and voids blocked by coagulation gel, and the effects of deterioration factors of reinforced concrete on those voids. [Diagram 2] FIG. 1 is a diagram showing the structure and electrical properties of colloidal silica. [Diagram 3] FIG. 13 is a schematic diagram showing (a) the ion surface potential, which is the zeta potential of CS silica particles, and (b) the correlation between the zeta potential of CS silica particles and the dispersion and aggregation of fine particles. [Figure 4] FIG. 1 shows (a) the dissolution state of CS at a given pH when the CS content is 10% and (b) the dissolution state of CS at a given pH when the CS content is 50%, according to one embodiment of the present invention. [Diagram 5] FIG. 13 is a graph showing particle size and zeta potential at the boundary pH for CS10% and CS50%. [Figure 6] FIG. 1 shows the correlation between the zeta potential of silica particles, dispersion and aggregation of fine particles, and the correlation between particle size for 10% CS. [Figure 7] FIG. 1 is a diagram showing the correlation between CS at a given pH and particle size distribution (frequency distribution) of silica particles. [Figure 8] This is a diagram showing coagulation (volume ratio mixing) due to acid rain. [Figure 9](a-1) is a schematic cross-sectional view of a hardened cement body having voids impregnated with CS and voids where the applied surface of the impregnated CS has gelled, (a-2) is a diagram showing the solution state of the gelled CS, and (b) is a diagram showing the water-stopping effect of carbonated CS compared to non-carbonated CS. [Figure 10] FIG. 1 shows the change over time in the state of solution of NaCl with salt concentrations of 3.1 to 3.8% in 10% CS (immediately after mixing and after 48 hours). [Figure 11] FIG. 13 is a graph showing the change over time of silica particles in 10% CS and NaCl with salinity of 3 to 3.45% (from immediately after mixing to 170 hours later). [Figure 12] FIG. 1 shows a test method for inhibiting the progress of neutralization by a CO2-derived gel. [Figure 13] FIG. 13 is a diagram showing the neutralization distance of the test results of FIG. 12. [Figure 14] FIG. 13 is a diagram showing the state of gel generated as a result of the test in FIG. 12. [Figure 15] FIG. 1 shows the results of evaluation of the surface protection state by a freezing method according to one embodiment of the present invention, which are differential scanning calorimetry (DSC) charts of (a) a hardened cement body treated with an impregnating material using salt water and (b) a hardened cement body treated with an impregnating material using CO2 treatment. [Figure 16] FIG. 16 is a diagram showing, similarly to FIG. 15, (a) a DSC chart of a hardened cement body impregnated with tap water and (b) a DSC chart of a hardened cement body impregnated with purified water. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments of the present invention will be described with reference to the drawings. The present invention is not limited to the following embodiments, and changes, modifications, and improvements can be made without departing from the scope of the invention.

[0012] As shown in Fig. 1(a) and (b), a structure of reinforced concrete 1 has voids 2 formed from a surface 5 toward its interior. Moisture (HO), chloride ions (Cl -), carbon dioxide (CO2), and other deterioration factors 3 penetrate from the surface 5 to the inside of the reinforced concrete 1, causing deterioration. If moisture (H2O) penetrates, it will promote corrosion of the reinforcing bars. - When carbon dioxide (CO2) is impregnated, it neutralizes the concrete, lowering its pH level, which in turn destroys the passive film on the reinforcing bars and promotes corrosion (deterioration).

[0013] Here, the reinforced concrete 1 has voids 12 and the like in addition to voids 2. Like voids 2, voids 12 are also formed from the surface 5 of the reinforced concrete 1 toward the inside, but when coagulation gel 4 is formed near the surface 5 in the region of voids 12 that extend from the surface 5 toward the inside, it is possible to inhibit deterioration factors 3 from permeating from the surface 5 to the inside. Therefore, by forming coagulation gel 4, it is possible to prevent deterioration of the reinforced concrete 1.

[0014] In the present invention, therefore, in order to prevent deterioration of the hardened cement body, an aggregate gel formed by promoting the aggregation of colloidal silica, which is one of the silicate-based surface impregnation materials, is utilized.

[0015] As shown in Figure 2, under basic conditions, the OH groups on the surface of the silica particles 6 of CS are converted to H + is released, resulting in the state shown in equation (1). (Formula 1) JPEG2025033243000002.jpg785 That is, the particle surface is negatively charged due to the progress of deprotonation of the silanol groups on the particle surface. The negatively charged silica particle surface is covered with cations to form an electric double layer 7.

[0016] When the direction of ion movement 9 of silica particles 6 that have formed an electric double layer 7 is as shown in Figure 3(a), the electric potential 8 of the ion surface is the zeta potential. The dispersion stability of silica particles in an aqueous solution is affected by the magnitude relationship between the repulsive force between particles due to the zeta potential and the attractive force due to the van der Waals force, and the correlation between the zeta potential (mV) and the dispersion and aggregation of silica particles (ions of silica particles) is as shown in Figure 3(b) ("Zeta Potential - Physical Chemistry of Fine Particle Interfaces: Scientist Press (2012)").

[0017] That is, when the zeta potential is between about -30mV and +30mV, the attractive force dominates over the repulsive force, and the silica particles (silica particle ions) are in an aggregated state. On the other hand, when the zeta potential is below about -30mV and above about +30mV, the repulsive force dominates over the attractive force, and the silica particles (silica particle ions) are in a dispersed state. EXAMPLES

[0018] As colloidal silica, a solution of commercially available CS (MS-90, manufactured by Nikken Co., Ltd., pH = 11.5) diluted to 10% (hereinafter sometimes referred to as "CS10%)" and a solution of commercially available CS diluted to 50% (hereinafter sometimes referred to as "CS50%)" were used.

[0019] (Preparation of test solutions) Hydrochloric acid (hereinafter sometimes referred to as "HCl") was used to examine the effect of pH on CS. The molar concentration of HClaq was adjusted to a specified pH after mixing CS with pH=11.5 and HClaq. 5 mL of CS was poured into a test bottle, and 5 mL of each solution was poured therein to mix. The mixed solution of CS and each solution was left to stand for 48 hours, after which various evaluation tests were performed.

[0020] (Various evaluation tests) In order to investigate the mechanism of coagulation by pH, concentration, and cations of CS, the following evaluation tests were carried out. (1) Particle size test using dynamic light scattering method In order to evaluate the aggregation state of silica particles contained in the mixed solutions of CS and various solutions, the particle size (volume basis) was measured using the dynamic light scattering method. The particle size measurement range of the device used is 0.3 to 10,000 nm. (2) Zeta potential test using electrophoretic light scattering method In order to evaluate the charge state of silica particles contained in CS and various mixed solutions, the zeta potential was measured using electrophoretic light scattering. As mentioned above, it is generally considered that when the absolute value of the zeta potential is greater than 30 mV, the particles are easily dispersed, and when it is less than 30 mV, the particles are easily aggregated.

[0021] Figure 4(a) shows the state of the test bottles 48 hours after mixing 10% CS and aq HCl. The mixed solution on the far left is pH=10, the mixed solution on the far right is pH=2, and the mixed solutions in between were pH=9-3 in increments of about 1. When checking the relationship between the pH and dispersion / aggregation of 10% CS in the figure, it can be seen that the mixed solution is in a dispersed state, as it is colorless and transparent, when the pH is between 10 and 6. On the other hand, when the pH is between 5 and 2, the mixed solution is in an aggregated state, as it is cloudy, and it is believed that there is a pH in the range of 6 to 5 at which aggregation begins.

[0022] Figure 4(b) shows the state of the test bottle 48 hours after mixing 50% CS and HClaq. As with the case of 10% CS, a mixed solution with a fine pH range between dispersion and aggregation was prepared so that the pH of the colorless, transparent dispersion state could be distinguished from the pH of the cloudy, aggregated state. From the state inside the test bottle, it is believed that aggregation of 50% CS begins at pH = 7.7.

[0023] In relation to Figure 4(a), Figure 5 shows the particle size distribution of CS as a function of pH. When pH = 10 to 8, the particle size of CS was 20 to 22 nm, and no increase in particle size due to aggregation was observed. When pH = 6.8, the particle size of CS was 28 to 30 nm, slightly larger than the particle size when pH = 10 to 8. When pH = 6.5, the particle size of CS was 70 to 90 nm, and since the particle size distribution range was wide, this is thought to be the boundary between dispersion and aggregation. When pH = 6.2, the particle size of CS was 1000 nm, 50 times the particle size of 20 nm before mixing.

[0024] FIG. 6 shows the correlation between dispersion and aggregation due to changes in pH and the particle size and zeta potential of silica particles for 10% CS.

[0025] Figure 7 shows the measurement results of particle size and zeta potential for CS10% and CS50% at each pH. Comparing the zeta potential for CS10% and CS50%, the zeta potential approached 0 mV as the pH decreased regardless of the dilution concentration. On the other hand, comparing the particle size for CS10% and CS50%, the particle size for CS10% increased at pH=6.5, but for CS50% increased at pH=7.7. From the above, it can be said that the higher the CS concentration, the higher the pH at which silica particles begin to aggregate.

[0026] From the above, it was found that it is possible to form a CS coagulation gel (silicic acid gel) by adjusting the concentration of CS (lowering the pH of CS), adjusting the CS concentration, and by contacting CS with chloride ions. Therefore, if CS is impregnated into the voids formed in the hardened cement body (e.g., reinforced concrete) and a CS coagulation gel (silicic acid gel) is formed near the surface of the hardened cement body, the voids are sealed by the coagulation gel (silicic acid gel), so to speak, and further impregnation (penetration) of deterioration factors of the hardened cement body can be prevented. As a result, deterioration of the hardened cement body can be prevented. In other words, it is possible to control the poison (deterioration of the hardened cement body (e.g., reinforced concrete) caused by the deterioration factor) with the poison (deterioration factor).

[0027] Here, as a method for lowering the pH of CS, i.e., a construction method, carbon dioxide present in the environment in which the cement hardened body is generally constructed, for example, in the atmosphere, can be used as a source for lowering the pH. Preferred sources for lowering the pH include acid rain, rivers, hot spring water, and carbon dioxide, and sources of carbon dioxide include gaseous carbon dioxide and carbonated water contained in groundwater. On the other hand, sources of chloride ions to be brought into contact with CS include salt water, preferably seawater, and rainwater containing snow-melting agents.

[0028] The case where the source of pH reduction was acid rain is as follows. CS and acid rain were mixed in the following volume ratio under the following conditions. 10% CS (5mL) was weighed into a test bottle and mixed with simulated acid rain (pH = 4). The pH of the mixed solution of CS and simulated acid rain was adjusted by increasing the volume ratio of the simulated acid rain as shown in Table 1. CS and simulated acid rain were mixed and left to stand for 48 hours, after which the particle size and zeta potential were measured. (Table 1) JPEG2025033243000003.jpg13154 The CS and zeta potential due to changes in the pH of the mixed solution are shown in Figure 8. The following can be seen from Figure 8. The particle size increases at pH levels below 6.5, with the pH of the mixed solution being the boundary at 6.5. This confirms that aggregation (gelation) of CS due to simulated acid rain (pH 4) occurs when the mixed solution has a pH of 6.5 or less.

[0029] The case where the source of pH reduction is carbon dioxide is as follows. As shown in FIG. 9(a-1), voids 32 are formed in the hardened cement body 21. When CS13 is impregnated into the voids 32 from the coating surface 15 of the hardened cement body 21, the voids 32 become voids 17 impregnated with CS13. Furthermore, when carbon dioxide (CO2) 19 is supplied from the coating surface 15 to the voids 17, CS13 changes to gel 14, and CS13 near the coating surface 15 changes to gel 14. Therefore, the voids 17 impregnated with CS13 become voids 18 impregnated with CS13, which have gel 14 near the coating surface 15. As a result, the voids 18 are in a state where the coating surface 15, i.e., the opening through which moisture and the like penetrates, is blocked by the gel 14.

[0030] The alkaline CS 13 is neutralized by carbon dioxide (CO2) 19 and turns into gel 14, and Fig. 9(a-2) shows gel 14', which is a reproduction of the state of gel 14 in a test tube. In gap 18, where the opening surface (applied surface 15) is blocked, the penetration of moisture and the like is suppressed compared to gap 17, which is not blocked.

[0031] Mortar (weight ratio: water: cement: sand = 1:1.8:4.7) hardened bodies (shaped like a square pillar, measuring 40 x 40 x 160 mm) were prepared. Two types of hardened bodies were prepared, one coated with CS and one uncoated. The CS-coated bodies were either carbonated for 8 weeks in an accelerated carbonation tank with a carbon dioxide concentration of 5% (CS carbonated) or not (CS uncarbonated). Moisture penetration tests were carried out on the three types mentioned above: uncoated, CS carbonated, and CS uncarbonated. As a result, as shown in Figure 9(b), when comparing the moisture permeability of CS carbonated and non-carbonated concrete compared to uncoated concrete, CS carbonated had a 40% suppression, or water-stopping effect, compared to CS non-carbonated.

[0032] In the case of seawater as a source of chloride ions to be brought into contact with CS, the procedure is as follows. 10% CS was mixed with NaCl solution of the same salt concentration as seawater, 3.1-3.8%. The mixing procedure was as follows. 10% CS (5 mL) and NaCl (5 mL) were mixed in a test bottle. As a result, as shown in Figure 10, it was found that a gel grew over time (after 48 hours) and that the gelation time differed depending on the salt concentration. Immediately after mixing, the solution was in a dispersed state at salt concentrations of 3.1-3.45%, but in an aggregated state at salt concentrations of 3.5-3.75%. In addition, as shown in Figure 11, it can be seen that the higher the salt concentration, the shorter the gelation time.

[0033] We conducted tests on a CO2-derived gel, which is produced by dissolving CO2 gas in an alkaline solution, which is a solvent for CS, and lowering the pH to produce a gel. As shown in Figure 12(a), the test method was to put CS10% (5mL) and Ca(OH)2aq (10%, 5mL) in a test tube and add PP (phenolphthalein test solution).Then, as shown in Figure 12(b), CO2 gas 19 was sealed in the top of each test solution every hour, and the distance of the gel 24 that was generated as the test solution neutralized from an alkaline state was measured as the neutralization distance.

[0034] As shown in Figure 13, the results of the neutralization distance showed that for 10% CS, the neutralization distance ranged from 0 mm to approximately 2 mm during the measurement time from 0 to 300 minutes, and remained constant after reaching approximately 2 mm (Gel 24

[60] ). On the other hand, for Ca(OH)2aq (10%, 5 mL), the neutralization distance increased almost linearly from 0 mm to approximately 50 mm according to the measurement time.

[0035] As shown in Figure 14, when observing CS10% for a measurement time of over 300 minutes up to 4320 minutes, it continued to grow slowly from Gel 24

[0360] to Gel 24

[4320] . When gel is formed, the rate of neutralization slows down, but it is estimated that the growth cannot be reduced to 0. Therefore, it is not thought that gel formation becomes difficult and water penetration becomes easier. Unlike when HClaq is mixed with CS10%, CO2 gas dissolves into CS10% from the gas phase that comes into contact with CS10% and generates gel through neutralization, so the generation of gel is gradual as described above.

[0036] (Preparation of hardened cement for freezing method) A hardened cement specimen (disk shape, 4mm diameter, 2mm thickness) was prepared to evaluate (measure) the surface protection state by the freezing method. The hardened cement specimen was either coated with CS or not. The hardened cement specimens were subjected to the following treatments (a) to (d). (a) CS was applied to a disk-shaped hardened cement body, which was then immersed in a 3% aqueous sodium chloride solution for 24 hours (Example 1). (a) CS was applied to the disk-shaped hardened cement body, which was then allowed to stand in a test tube filled with carbon dioxide gas for 7 days (Example 2). (c) A disk of hardened cement without CS coating was immersed in tap water for 24 hours (Comparative Example 1). (d) A disk of hardened cement without CS coating was immersed in purified water for 24 hours (Comparative Example 2). That is, the impregnating material-treated hardened cement body was prepared by steps (a) and (b).

[0037] (Evaluation by freezing method) The hardened cement bodies of Example 1 to Comparative Example 2 were subjected to evaluation (measurement) of the surface protection state by the freezing method as follows. Using a differential scanning calorimeter, the amount of heat generated and absorbed was measured during the freezing process from 10°C to -60°C and during the thawing process from -60°C to 10°C. The rate of the freezing and thawing process was 5°C / min. The evaluations (measurements) of Example 1, Example 2, Comparative Example 1, and Comparative Example 2 are Measurement Example 1, Measurement Example 2, Comparative Measurement Example 1, and Comparative Measurement Example 2, respectively.

[0038] The measurement results are explained as follows using the differential scanning calorimetry (DSC) chart of the measurement results of Measurement Example 1 shown in FIG. 15(a) as an example. The vertical axis of the DSC chart is heat flow (mW) and the horizontal axis is temperature (°C). The temperature of the measurement object is cooled from about 10°C to more than about -60°C to freeze (freezing process), and then the temperature is raised to about 10°C to melt (melting process) and measured. Then, in the freezing process, when the temperature is between -15°C and -20°C, a large exothermic peak of positive heat flow (mW) was detected due to the freezing of moisture in pores with a diameter of 10 nm to 8 nm. Then, in the melting process, a peak of negative heat flow (mW) was detected at a temperature of about 0°C. The peak in the melting process (negative value) is not used to interpret the data because the two peaks of moisture in the large diameter pores and moisture in the small diameter pores in the freezing process (positive value) are not separated.

[0039] 16(a), in addition to the first and third peaks, a small peak of positive heat flow (mW) due to freezing of water in voids with a diameter of 4 nm to 3 nm was detected at temperatures between -37° C. and -47° C. In addition, the temperature ranges in which the first and third peaks of Measurement Example 1 appear and the temperature ranges in which the first and third peaks of Comparative Measurement Example 1 appear are slightly different, but since the physical causes of the appearance of these peaks are the same as described above, there is no need to consider the difference in temperature ranges.

[0040] From the viewpoint of appropriately detecting the peak, the temperature range of the measurement is preferably from 5°C to -50°C, and more preferably from 10°C to -60°C.

[0041] Comparing the differential scanning calorimetry (DSC) charts of Figure 15(a) (Measurement Example 1) and Figure 15(b) (Measurement Example 2) with the DSC charts of Figure 16(a) (Comparative Measurement Example 1) and Figure 16(b) (Comparative Measurement Example 2), it can be seen that the second peak was not detected in Measurement Examples 1 and 2, but was detected in Comparative Measurement Examples 1 and 2. In other words, small diameter voids were detected in Comparative Measurement Examples 1 and 2, but not in Measurement Examples 1 and 2. The reason for this is presumed to be that the gel formed by CS blocked the large diameter voids, thereby suppressing the penetration of moisture into the small diameter voids.

[0042] A further explanation is as follows. If small voids are filled with gel, the moisture contained in the gel will also be detected by the freezing method, and so the second peak will be detected. It is presumed that the moisture detected in large voids (first peak) is gel, and that the formation of gel in the large voids prevents moisture from penetrating into the small voids behind them, which is why the second peak did not appear. Filling large voids with gel itself prevents moisture from penetrating into the interior, and is therefore beneficial for improving the durability of the hardened cement body. Therefore, the freezing method can be used to evaluate the surface protection state of the hardened cement body (hardened cement body treated with impregnation material). [Industrial Applicability]

[0043] Since the concrete deterioration factor can form a protective layer, it can be used for repairing concrete structures, and the condition of the repair can be evaluated. [Explanation of symbols]

[0044] 1: Reinforced concrete 2, 12, 32, 42: void 3: Deterioration factor 4, 14, 14', 24, 24

[60] , Gel 24

[4320] : Aggregated gel (gel) 5: Surface of reinforced concrete 6: Silica particles 7: Electric double layer 8: Electric potential of ionic surface 9: Ion travel direction 13: Colloidal silica (CS) 17: Voids impregnated with CS 15: Coating surface (opening surface) 18: Impregnated CS, with the gelled CS near the coating surface impregnated in the gap 19:CO2 gas 21: Hardened cement

Claims

1. A surface impregnation method carried out for protecting the surface of a hardened cement body with a surface impregnation material, the method comprising: an impregnation step of impregnating voids formed on the surface of the hardened cement body with colloidal silica as a surface impregnation material; and a pH reducing step of contacting the colloidal silica with a pH reducing material that reduces the pH of the impregnated colloidal silica after the impregnation step, and / or a contacting step of contacting the impregnated colloidal silica with chloride ions.

2. 2. The surface impregnation method according to claim 1, wherein the pH lowering agent is a substance that provides hydrogen ions to the colloidal silica.

3. 2. The method according to claim 1, wherein the chloride ions are provided by a salt containing chloride ions.

4. 2. A method for evaluating a surface protection state of a hardened cement body as described in claim 1, comprising the steps of freezing, under the same conditions, the hardened cement body having voids on its surface and containing moisture, and an impregnating-material-treated hardened cement body which has been subjected to a surface impregnation treatment with a surface impregnation material, as evaluation objects, and comparing the measurement results of the heat flow (mW) of both the hardened cement bodies to evaluate the state of blocking of the voids by the surface impregnation material.

5. The evaluation method according to claim 4, wherein the same conditions include a temperature range of at least 5°C to -50°C.

6. The evaluation method according to claim 4 or 5, wherein the surface impregnation material is colloidal silica.

7. 6. An evaluation method for determining that a measurement object for which the lowest temperature peak is not measured among the peaks detected in the hardened cement body by the evaluation method according to claim 5 is a hardened cement body treated with an impregnating material.

8. 7. An evaluation method for determining that a measurement object for which the lowest temperature peak is not measured among the peaks detected in the hardened cement body by the evaluation method according to claim 6 is a hardened cement body treated with an impregnating material.

Citation Information

Patent Citations

  • Concrete to be modified, concrete structure to be modified, and method for modifying concrete

    JP2022079810A